(untitled) (Research, Society and Development, 2023)
Pressure ulcers (PU) are a health problem that has been a cause for concern because they represent a public health problem. It is known that care for people with LP should occur in high and medium complexity, but also in Primary Health Care, under the care of the Family Health Team. This study aims to synthesize findings from the Brazilian scientific literature about nursing care in the prevention of GP in the Family Health Strategy. This is a narrative review study, with a bibliographic survey carried out in the electronic databases of the Virtual Health Library (VHL). The descriptors "Pressure Sores", "Family Health Strategy" and "Nursing", obtained from the Descriptors in Health Sciences (DeCS), were the search guides. In addition, the Boolean operator "AND" was applied. The systematic review included 06 articles. It was evident in the studies that most nurses do not use a specific method for evaluating LPs, which is sometimes done based on previous knowledge. Thus, we realized the importance of professional qualification for nursing care to patients with LP in the ESF, both in order to implement preventive measures to identify the risk of new lesions, and in the care of existing lesions. Institutional protocols to guide this care are also relevant. Thus, regarding the performance of the FHS nurse, the professional’s training and search for knowledge are essential for improving care.